Evaluation of an emergency department‐based approach to reduce subsequent opioid overdoses - Eric N. Reed; Joan Papp; Yesol Oh; Kellie LeVine; Yasir Tarabichi; Estella Bastian; Kailee Pollock; Lance D. Wilson; Jonathan Siff; Joseph S. Piktel (Journal of the American College of Emergency Physicians Open)
Abstract Objective The purpose of this study was to determine the association of a multi‐pronged treatment program in emergency department (ED) patients with an acute presentation of opioid use disorder (OUD) on the rate of subsequent opioid overdose (OD). This approach included ED‐initiated take‐home naloxone, prescription buprenorphine, and an ED‐based peer support and recovery program. Methods This was a retrospective observational analysis of adult patients presenting to the ED at a large urban hospital system from November 1, 2017 to March 17, 2023. Patients with an ED discharge diagnosis of OD or OUD were included. Outcomes determined were subsequent 90‐day OD and 180‐day OD death. Post hoc analyses were performed to identify intervention utilization throughout the study period including the COVID‐19 pandemic as well as ED characteristics associated with subsequent OD and OD death. Statistical comparisons were made using logistic regression and chi‐squared test. Results A total of 2634 patients presented to the ED with an opioid OD or diagnosis of OUD. Subsequent 90‐day OD decreased significantly over time (11.5%–2.3%, odds ratio [OR] 0.85, confidence interval [CI] 0.82–0.89). No single intervention was independently associated with 90‐day OD or 180‐day OD death. Resource utilization was stable during the COVID‐19 pandemic and increased afterward. A higher buprenorphine fill‐rate among all patients and the Back race subgroup was associated with a decrease in 90‐day OD. Conclusions Subsequent OD and OD death decreased over time after implementation of a multi‐pronged treatment program to ED patients with OUD. No single intervention was associated with a decrease of subsequent OD or OD death.